Investigação de mutações nos genes LEPRE1, CRTAP, PPIB, FKBP10, SERPINH1 e SERPINF1 causadoras da osteogênese imperfeita recessiva - Furtado, Clara Fernanda Barbirato (2015)
Osteogenesis Imperfecta (OI) is a clinically and genetically heterogeneous disease predominantly characterized by bone fragility and deformity and recurrent fractures. Most cases of OI result of autosomal dominant mutations in COL1A1 and COL1A2 genes that encode the chains forming type I collagen, the main protein in bones. In the past few years, an increasing number of cases due to recessive mutations has been reported in genes associated with the biosynthesis of type I collagen or to the formation and bone mineralization, such as LEPRE1, CRTAP, PPIB, FKBP10, SERPINH1 and SERPINF1. Mutations in these genes, in general, lead to the development of severe and lethal OI phenotypes. In this work, LEPRE1, CRTAP, PPIB, FKBP10, SERPINH1 and SERPINF1 of 25 OI patients were analyzed using SSCP and automated sequencing. Altogether, 29 genetic variations were detected, mutations and polymorphisms. Among the eleven variants found in LEPRE1 gene, there are the already well described c.1080 + 1G> T and the potentially deleterious mutations c.2024G> A / p.Lys363Glu and c.1501C> T / p.Arg501Trp . In FKBP10 gene, the previously described duplication c.831dupC, and c.1546G>A / p.Leu516Phe, predicted to be disease causing, were detected. It was observed that FKBP10 and LEPRE1 contain the most important mutations found in the patients studied in this work and it is suggested that LEPRE1 and FKBP10 should be preferably analyzed in studies of screening and identification of mutations in patients with OI. To date, there are no reports of mutations in LEPRE1, CRTAP, PPIB, FKBP10, SERPINH1 and SERPINF1 genes in Brazilian patients and this study provides new information on the genetic aspects of recessive OI.